P12.06 Unmet needs and wish for support of informal caregivers of primary brain tumour patients. (9th September 2021) - Pointon, L; Grant, R; Peoples, S; Erridge, S; Sherwood, P; Klein, M; Boele, F
Abstract: BACKGROUND: Most primary brain tumour patients rely on informal caregivers (i.e. family members or friends) for practical and emotional support. While caregiving can be rewarding, it also commonly leads to significant burden. In developing support for caregivers, it is vital to distinguish between caregivers' unmet needs, and their actual wish for support to resolve unmet needs. We aimed to 1) identify the presence and magnitude of unmet needs; 2) examine associations between unmet needs and desire for support; 3) evaluate perceived usefulness of caregiver needs screening in clinical practice. MATERIAL AND METHODS: Family caregivers of patients with primary brain tumours were recruited and asked to complete an adapted version of the Caregiver Needs Screen (CNS). This covered the level of distress resulting from 33 common issues in neuro-oncology caregiving (scale 0–10), and wish for information or support for any issue (yes/no). In addition, participants were asked to rank (0–7) their experience of using the CNS based on items covering 'ease of us', 'usefulness' and 'satisfaction'. Descriptive and correlational analyses were applied. RESULTS: Caregivers ( N =79) reported between 1–33 unmet needs (M=17.20, sd=7.98) but did not always wish for support for each need (range 0–28, M=4.71, sd=6.63). Most distressing items were patient's fatigue (M=5.58), recognising signs of disease progression (M=5.23), changes in patients' thinking or behaviour (M=5.04), patient distress or sadness (M=4.68), and changes in caregivers' own emotional health (M=4.44). A weak correlation was found between the total number of unmet needs and the desire for support ( r =0.296, p =0.014). Caregivers most often desired support with recognising disease progression ( N =24), managing medications and side-effects ( N =18), and least often with managing spiritual issues ( N =0), communication with (grand)children ( N =2) and communication with family members and friends ( N =3). Caregivers evaluated the CNS tool positively (mean item scores ranging 4.19–6.21 out of 7). CONCLUSION: Family caregivers of brain tumour patients experience distress resulting from many neuro-oncology specific needs, but this is not directly related to a wish for support or information. Caregiver needs screening could be useful to tailor support or information to suit caregivers' preferences in clinical practice.